2022
DOI: 10.12913/22998624/152527
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Filters Filled with Rockfos for Phosphorus Removal from Domestic Sewage

Abstract: The goal of the present study was to evaluate the efficiency of filters filled with Rockfos for removal of phosphorus (Total-P) from domestic wastewater. Rockfos is a material obtained by calcination of carbonate-silica rock (opoka) at a temperature of 900 °C. A field study was conducted in two filters with volumes of 2.0 and 0.8 m 3 which were components of hybrid constructed wetlands with an average capacity of 2.0 m 3 /L, located in two national parks in south eastern Poland. Samples of the influent to and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 33 publications
(45 reference statements)
2
12
0
Order By: Relevance
“…Laboratory studies indicate that, with this material and a sufficiently long contact time, it is possible to remove more than 90% of the total phosphorus from wastewater [12]. In contrast, preliminary studies conducted on a full technical scale have shown a phosphorus removal efficiency of about 40% [18]. The efficiency of phosphorus sorption depends mainly on the flow conditions and the contact time of the wastewater with the sorption material; hence, the plants in operation are most often in the form of chambers with the forced vertical sewage flow through the filter bed [18].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Laboratory studies indicate that, with this material and a sufficiently long contact time, it is possible to remove more than 90% of the total phosphorus from wastewater [12]. In contrast, preliminary studies conducted on a full technical scale have shown a phosphorus removal efficiency of about 40% [18]. The efficiency of phosphorus sorption depends mainly on the flow conditions and the contact time of the wastewater with the sorption material; hence, the plants in operation are most often in the form of chambers with the forced vertical sewage flow through the filter bed [18].…”
Section: Introductionmentioning
confidence: 99%
“…This method of phosphorus removal is used in wastewater treatment plants at the end of the process line when the wastewater is already free of organic pollutants. In the literature, one can find publications in which various minerals and reactive materials were studied [14][15][16][17][18][19][20][21][22]. Among them, carbonatesilica rock (ophiolite) has also been mentioned as a sorbent with a high capacity to absorb phosphorus [12,18,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A particular example of this is sulfur borehole mining, which involves melting sulfur in the depths of the earth and bringing it to the surface in a closed pipeline system (Frash method). The seemingly safe method caused intensive degradation and devastation of the environment as a result of numerous failures, as well as deterioration of chemical, physicochemical, physical and biological properties [1][2]. The process is all the more intense as it concerns the environment with weak and defective native soils [1,[3][4].…”
Section: Introductionmentioning
confidence: 99%